2013
DOI: 10.1177/0192513x13516763
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Relationship Between Instability in Child Care and Instability in Employment for Families With Subsidized Care

Abstract: Through the federal child care funding and unspent Temporary Assistance to Needy Families funds, states provide subsidies for child care to some employed parents who are income-eligible. Subsidies cannot alter labor market conditions or stabilize low-wage jobs, but they can stabilize child care arrangements. With stable child care, policy makers hope parents’ workforce participation will be more stable. While researchers agree there is a strong relationship between stability in child care and stability in empl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Research that has attempted to tease apart the influence of job instability on childcare instability and vice versa suggests the relationship is quite nuanced. Childcare disruptions can be detrimental to job stability, but more frequently job changes precipitate childcare changes (Miller 2006;Scott and Abelson 2016). Also, parents with precarious work schedules are more likely to have difficulty arranging childcare and to miss work because of lack of care, potentially threatening their employment (Luhr, Schneider, and Harknett 2022, this issue).…”
Section: W H Y Childca Re Continuit Y M At Tersmentioning
confidence: 99%
“…Research that has attempted to tease apart the influence of job instability on childcare instability and vice versa suggests the relationship is quite nuanced. Childcare disruptions can be detrimental to job stability, but more frequently job changes precipitate childcare changes (Miller 2006;Scott and Abelson 2016). Also, parents with precarious work schedules are more likely to have difficulty arranging childcare and to miss work because of lack of care, potentially threatening their employment (Luhr, Schneider, and Harknett 2022, this issue).…”
Section: W H Y Childca Re Continuit Y M At Tersmentioning
confidence: 99%
“…Prior research has found that child care‐related work disruptions are less likely to occur when the parent is receiving child care subsidy (Forry & Hofferth, ), which could also potentially reduce parenting stress. In this, considering that poverty has long been seen as a risk factor for poor parenting behaviour (Conger & Elder, ; Conger, Ge, Elder, Lorenz, & Simons, ), the employment stability associated with subsidized child care (Scott & Abelson, ) and increase in hours worked (Press, Fagan, & Laughlin, ) could prevent child maltreatment from occurring. Further, child care subsidy has been found to be related to reduced placement disruptions for children in foster care (Meloy & Phillips, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The provision of basic needs and services can be destabilized by both income instability and the loss of public benefits. Growing evidence from both qualitative studies and surveys documents the high frequency of change in lowincome family life and the linkage between change in employment and change in child care (Scott, London, and Hurst 2005;Ben-Ishai, Matthews, and Levin-Epstein 2014;Scott and Abelson 2016) and change in employment and change in housing (Desmond and Gershenson 2016).…”
Section: Interactions Between Domainsmentioning
confidence: 99%